Impact of Welfare and Unemployment on the Crimes in the United States: Co-integration Analysis - MOURAD, Mahmoud (Journal of Public Administration and Governance, 2023)
The paper carries out a depth study of the total annual crimes by 100000 people in the United States, considered as the dependent variable, and two explanatory variables that are: welfare expenditure by 100000 people and unemployment rate during the period 1980-1919. The paper is oriented to a specific point: impact the unemployment and welfare variables on the total crimes (violent and property) in the United States of America. Much attention is given to the stationarity analysis and then to the cointegration analysis using the ARDL / Bounds testing Methodology proposed by Pesaran, Shin and Smith (PSS). Two long-term equilibrium relationships were identified and an interpretation of the results was performed. Both relationships have been validated and the Error Correction Model (ECM) is built. The results show that the adjustment speeds towards equilibrium are in the case of Unrestricted intercept and no trend, and in the case of Unrestricted intercept and trend.